Biarticular leg muscles and links to running economy - Heise, G.; Shinohara, M.; Binks, L. (International Journal of Sports Medicine, 2008)
Relationships between an index of running economy (V?O2 per distance) and the temporal electromyographic characteristics of leg muscles were quantified in female runners. Sixteen women performed a 30-min treadmill run at a speed designed to elicit a hard rating of perceived of exertion. Near the end of the run, oxygen uptake, video, and electromyographic data were collected simultaneously. Measures of muscle on-time durations, and on-time coactivation durations were calculated from the following muscles: gastrocnemius, vastus lateralis, rectus femoris, and biceps femoris. Nonparametric correlations between V?O2 per distance and temporal electromyographic data were evaluated. Greater on-time duration of rectus femoris during stance, and greater on-time coactivation duration of rectus femoris-gastrocnemius during stance were significantly associated with more economical runners (i.e., lower V?O2 per distance). The coactivation of biarticular leg muscles during stance is clearly linked to running economy and this control strategy may elicit greater elastic energy return.